The Relationship between Physical Activity and Omega-3 Fatty Acid Consumption with the Level of Dysmenorrhoea in Adolescent Girls at SMP PGRI 8 Denpasar - Annisa Ayu Herika; Ni Nengah Ariati; Ni Made Dewantari; IGA Ari Widarti; Gusti Ayu Dewi Kusumayanti (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
Lack of physical activity and consumption of omega-3 fatty acids can be one of the factors causing dysmenorrhea. This study aims to determine the relationship physical activity and consumption of omega-3 fatty acids with the level of dysmenorrhea in female students at SMP PGRI 8 Denpasar. This research is observational with a cross-sectional design.The sample size was 62 people according to the inclusion criteria, namely being registered as active students, willing to be a sample, having menstruation, not sick, and aged 12-18 years old. Physical activity data were collected using the GPAQ, level ofdysmenorrheausing the NRS and consumption of omega 3 fatty acids using the SSQFFQ form. Statistical analysis used is the Spearman rank correlation test (α=0.05).The results showed that 51.6% of the samples had low activity, 32.3% consumed omega-3 fatty acids in the category of severe and moderate deficits and 54.8% with moderate dysmenorrhea, and 11.3% severe. The results of the statistical analysis showed that there was a relationship between physical activity and consumption of omega-3 fatty acids with the level of dysmenorrhea (p0.05).It is recommended for young women to do regular physical activity and consume enough omega-3 fatty acids to prevent dysmenorrhea.